Psychological well-being and academic achievement of Minang students viewed from family structure and living arrangements - Hartati, Niken; Adiyanti, Maria Goretti; Mirza, Wenty Marina; Yuniarti, Kwartarini Wahyu (Indigenous, 2021)
Abstract. Previous research has proven that individuals raised in intact family structures have better psychological well-being and academic achievement than those raised in non-intact families. However, these findings emphasize only the nuclear family and have not considered the living arrangement factor that allows social support from extended families such as those in the Minang community. This study involved N = 201 students of Minang ethnicity from intact families (n = 160) and non-intact families (n = 41) who lived with nuclear families (n = 162) and extended families (n = 39). The sampling technique was carried out with convenient sampling. The instrument used is the translated Ryff's PWB(Psychological Well-Being) scale with a reliability of 0.912. Meanwhile, data on academic achievement was obtained through the participants' IPK (cumulative grade point index). Family structure data is obtained from participants' answers to the marital status of biological parents. The living arrangement data is obtained from the answer to whom the participants live with to determine the presence/absence of extended family members in their home. The analysis showed no differences in psychological well-being and academic achievement regarding family structure and living arrangements. However, the interactionsbetween groups showed differences in PWB between groups of participants from intact families and groups of non-intact families who lived with only nuclear families. This research shows the importance of paying attention to the context of the participants' socio-cultural environment, producing different conclusions from previous findingsKeywords: academic achievement; extended family; intact family; Minang; non-intact family; nuclear family; psychological well-being.